LITERACY BASED TEACHING IN READING RECOUNT TEXT BY USING AUTHENTIC MATERIALS - Wini Widianti Rifa’i; Rina Herlina (Universitas Galuh, 2021)
This study deals with the development of authentic materials in teaching reading recount text in literacy-based teaching. This study was aimed at 1) observing how the teacher develops recount text by using authentic materials in the literacy-based teaching, and 2) figuring out the students’ responses on authentic materials in recount text developed in the literacy-based teaching. This study employed a qualitative method with the type of case study design. By using purposive sampling technique, this study involved 23 students of class VIII-D and the English teacher is the sample of this study. The research instruments used in this study were the classroom observation, interview, and questionnaires. This study used the triangulation to analyze the data. The result revealed that the teacher used only five of seven principles of literacy in developing authentic materials in teaching reading recount text. They are interpretation, collaboration, problem solving, reflection and self-reflection; and literacy involves language use. Furthermore, the use of authentic materials in reading recount text improved the students’ motivation and reading comprehension. Meanwhile, the use of authentic materials also helped them to overcome their difficulties in learning reading, improving students’ vocabulary, and enhancing the students’ attention in learning reading. It can be concluded that the use of authentic materials by using some principles of literacy has given positive effect to the student’s motivation and reading comprehension. Authentic material is one of media which can help and facilitate the students in a reading text. Keywords: Literacy based teaching, reading, recount text, and authentic materials.